A Computer Program to Determine the Resistance of Long Wires and Rods to Nonhomogeneous Ground - Arcone,Steven A (1977)
A computer program was developed for finding the d-c resistance to ground of two simple electrodes, a straight horizontal wire and a vertically driven rod. The objective of this study was to develop a rapid means of finding the resistance to ground of simple electrode types in arctic environments where a two-layer earth model, frozen and unfrozen ground, is applicable. The program can consider homogeneous as well as two-layer earth, and the length, diameter and position of the electrodes. The computations were performed first by dividing an electrode into several smaller segments. Next the electrostatic potential of each segment was computed at the center of the electrode for unit-applied current. The segment potentials were then summed to find the total resistance to ground. Some specific computations are presented in comparison with previous theoretical work of other authors. The following conclusions were made: 1) A maximum run time of 165 seconds is needed for all two-layer arctic models where (a) the depth of the upper layer does not exceed 10 m, (b) the vertical rod length is less than 30 m, or (c) the horizontal wire length is less than 100 m; 2) Best accuracy is obtained when rod and wire radii are less than 0.01 m; and 3) Coincidence of the center of the vertical electrode with the two-layer interface must be avoided. (Author)